Effects of excretion care with a smart automatic defecation treatment system on skin humidity, incontinence-associated dermatitis, and pressure ulcers of patients with incontinence residing in long-term care facilities: Non-equivalent control group non-synchronized design. - Eun-Ju Kim; Eun-Young Kim (Journal of Korean Gerontological Nursing, 2023)
Purpose: This study investigated the effects of excretion care using a smart automatic defecation treatment system on skin humidity, pressure ulcer (PU) occurrence, and severity of incontinence-associated dermatitis (IAD) among patients with incontinence residing in long-term care facilities. Methods: Each patient in the experimental group was fitted with a smart automatic defecation treatment system. The system detected the release of urine/stool via a built-in sensor, followed by suction, cleaning with a water jet, and drying with warm air. Incontinence management for the control group involved the use of wet wipes for cleaning and changing diapers. The nursing interventions lasted for 2 weeks, and data were collected at baseline, week 1, and week 2. Descriptive statistics, t-tests, and the repeated-measures analysis of variance were used for data analysis. Results: The analysis revealed statistically significant differences in skin humidity and IAD between the experimental and control groups. Conclusion: This study is pertinent because it demonstrated the positive effects of excretion care using a smart automatic defecation treatment system on skin humidity, PU risk, and IAD among patients with incontinence residing in long-term care facilities. Further research is necessary to investigate additional factors such as pressure and physiological traits.